Self-deception - Galgut, Elisa Lynn (My University, 1991)
The topic of this dissertation is self-deception. It involves a general analysis of the problem, however, the central discussion centres on an agency-type approach to the problem, and in particular on Freudian-type approach.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in partial fulfilment of the Degree of Master of Arts.
Keywords: Freud, Sigmund, 1856-1939.; Self-deception.